Biocrusts do not harm shrub root water uptake in the Mu Us sandland, China - Hongjie Guan; Yang Yu; Mengqi Yin; Sizhuo Guo; Gernot Bodner (Journal of Hydrology: Regional Studies)
Study regions: Three study sites (Yanchi, Wushen, and Yijinhuoluo), located in the Mu Us sandland, China. Study focus: Effects of biocrusts on the actual evapotranspiration (ETa) and transpiration (Ta) of Artemisia ordosica in the Mu Us sandland were determined and its effects on water stress along a precipitation gradient were simulated based on in-situ field monitoring and two-dimensional model. New hydrological insights for the region: Our study revealed that: (i) A. ordosica with biocrusts had a significantly higher ETa and Ta as compared to the A. ordosica with bare soil; however, biocrusts decreased the evaporation (Ea) by 7.1 %, 11.4 %, and 13.1 % for the cyanobacteria, lichens, and mosses, respectively, although the effects of biocrusts on the Ea were nonsignificant. (ii) compared to uncrusted soil, biocrusts decreased soil evaporation by 6.1 % but increased plant water uptake (PWU) by 16.1 %, (iii) soil moisture was increased by 5.4 %, 5.1 %, and 4.8 %, whereas the water stress fraction of the season was reduced by 22.7 %, 29.8 %, and 28.1 % for the Yanchi, Wushen, and Yijinhuoluo sites, respectively, as a results of biocrusts, and (iv) with an increasing seasonal rainfall amount, the PWU ratio decreased, with the mean value of 1.20, 1.17, and 1.15 for the Yanchi, Wushen, and Yijinhuoluo sites, respectively. Our results showed that biocrusts do not adversely affect root water uptake in drylands; hence, it is necessary to reconsider and re-evaluate the current vegetation restoration strategy in the perspective of biocrusts and plant water availability, in which shrubland were selected on a large scale in the arid regions.